Design of a Prototype of Soil Condition Monitoring System Based on Telegram Messenger Bot - Muhammad Rizal Mahdifikia; Mifta Nur Farid; Himawan Wicaksono (Jurnal Sistim Informasi dan Teknologi, 2022)
Balikpapan City has a moderate level of vulnerability to landslides. This is because the city of Balikpapan has the triggering factors and causes of landslides. The trigger factor is a tropical climate with high rainfall of 2,887 mm/year. While the causative factor is that 85% of the Balikpapan City area consists of hilly areas. Therefore, it is necessary to conduct research monitoring soil conditions. This study uses several sensors such as the MPU6050 sensor, Capacitive Soil Moisture V1.2 sensor, buzzer, and the NodeMcu ESP8266 microcontroller. This prototype acts as an early warning system. The buzzer on the prototype will sound if the landslide hazard condition is identified. In addition, this prototype sends data on soil conditions via the Telegram Messenger Bot on the Telegram Messenger application. The results of data collection when the slope of the soil is 10o to 30o, the condition of the soil does not vibrate, and the soil moisture is dry is that there is no landslide. However, when the slope is 40o to 50o and the soil moisture is dry, the result is a landslide. For the data results when the slope is 10-40o, the soil condition does not vibrate, and the soil moisture is moist, there is no landslide. However, at a slope of 50o and moist soil moisture, landslides occur. For data results with a slope of 10o - 50o, the condition of the soil does not vibrate and the moisture of the wet soil is that there is no landslide. For the data results when water is flowed directly using a water hose at a slope of 10o to 30o and the ground does not vibrate is that there is no landslide. However, at a slope of 40o to 50o, the ground does not vibrate and landslides occur.